The Effect of Foreign Currency Derivatives, Foreign Debt, and Foreign Business Operations on Exchange Rate Exposure of Euro-Era German Firms - Minicucci, Daniel (2017)
Using public data, this study examines the effects of foreign business operations, foreign currency derivative use, and foreign debt use on exchange rate exposure of nonfinancial German firms listed on the DAX 30 market index. The results demonstrate that five firms, or approximately 22% of the sample, have stock prices that are significantly tied to exchange rate fluctuations. The results also demonstrate that foreign business operations and foreign currency derivative use are appropriate estimators of exchange rate exposure. In addition, this study finds that foreign business operations are inversely related to firms that exhibit negative exchange rate exposure. This study produces inconclusive results regarding the effect of foreign debt use on exchange rate exposure.